INTERACTIVE TECHNOLOGY IN THE TEACHING AND LEARNING PROCESS IN HIGHER EDUCATION - Touriano, Derist (LPPM Universitasdiwangsa Jambi, 2018)
An important aspect that requires great attention in each college is related to the lack of educational facilities and the low interest in student learning which risks the education process. Therefore the purpose of this study is to develop an interactive learning technology so that the lecturers are more creative in providing explanations of lecture material not to go monotonous and exciting. This research method is divided into four stages from ten stages of research and development to solve research problems. The final conclusion of this study is use interactive learning technology, especially SmartBoard, is easy to implement with low cost so that lectures and students can explore information more effectively and efficiently.